ACTION RESEARCH IN EDUCATION - Kaur, Surnider (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Action research is a practical approach to professional inquiry in any social situation. The examples in this component relate to education and are therefore of particular relevance to teachers or lecturers engaged in their daily contact with children or students. But professional practice need not be teaching: it may be management or administration in a school or college, or it may be in an unrelated area, such as medicine or the social services. The context for professional inquiry might change, but the principles and processes involved in action research are the same, regardless of the nature of the practice. Indeed, action research did not arise in education (see Lewin, 1948), but was applied to the development of teaching as its potential was identified. Of particular influence was the work of Lawrence Stenhouse, who famously advocated that curriculum research and development ought to belong to the teacher (Stenhouse, 1975, p. 142). He was most adamant that it is not enough that teachers work should be studied: they need to study it themselves. The aim of an action researcher is to bring about development in his or her practice by analyzing existing practice and identifying elements for change. The process is founded on the gathering of evidence on which to make informed rather than intuitive judgements and decisions. Perhaps the most important aspect of action research is that the process enhances teachers professional development through the fostering of their capability as professional knowledge makers, rather than simply as professional knowledge users. In an age of centralization and the proliferation of national guidelines and strategies, action research can help teachers feel in control of their own professional situation. Action research therefore has two aspects. The starting point is to sort out a problem or issue in practice; to this extent an action researcher seeks a solution. But the process can also be used as a deliberate attempt to understand practice better-a traditional research attitude. What is most important in both approaches is that you are open, honest and rigorous. From the perspective of action research, the best way to think about practice is the way you carry out your professional actions. This, of course, what you do, but it is also why you think you should be doing things the way you do. You will hear of the theory-practice divide; action research as an approach cuts this divide, encouraging a practitioner to consider both aspects as part of a single whole.